Analisis Kemampuan Mengungkapkan Bahasa Anak Usia 5-6 Tahun Melalui Media Film Animasi - St. Hajra Ulfa; Besse Marjani Alwi; Baharuddin (NANAEKE: Indonesian Journal on Early Childhood Education, 2023)
Early childhood is a child who is still in a period of growth and development. One important aspect of development is language. Language is a communication tool in the form of symbols or sounds produced by human language tools. There are many ways that teachers can develop children's language, one of which is using animated film media. Animated film media is a combination of audio and visual which contains a series of still images, but is projected by an electronic device. This research aims to determine the ability to express language in children aged 5-6 years through the medium of animated films at Kindergarten Ceria Desa Terasa District. West Sinjai District. Sinjai. This descriptive type of qualitative research has as subjects 10 children aged 5-6 years. Data collection uses interviews, observation, and documentation. Data analysis techniques Data reduction, data display, and concluding. The results of the research show that the ability to express language in children aged 5-6 years through the medium of animated films at the Ceria Desa Terasa Kindergarten, Kec. West Sinjai District. Sinjai also has not developed according to expectations, this is because teachers do not follow the steps for applying animated film media, even though to make the use of animated film media more interesting, you must pay attention to how the media is applied.